The Lecturers’ Strategies in Teaching Reading Comprehension for Management Students - Dwi Handayani Silitonga (PT Inovasi Pratama Internasional, 2022)
English is one of the subjects taught at the university level, as well for management study program at the STIE Bina Karya, where the students focus their learning not on English, but have to take English courses as a general subject. This study aimed to find out what strategies are applied by lecturers in teaching reading comprehension for management students at STIE Bina Karya. The participants of this research are two English lecturers at STIE Bina Karya. This descriptive qualitative design applied a questionnaire for collecting the data. The result of this research showed that there are some different activities were carried out by the two lecturers at the while-reading stage. The first lecturer prefers to ask students to read the text one by one to improve their pronunciation. However, sometimes she asked them to read the text silently. Meanwhile, another lecturer prefers asking the students to read silently to gain better comprehension. Moreover, both lecturers agreed that in pre-reading activities, lecturers have to first use a strategy to attract students' interest in learning English and make it easier for them to understand the material content. For measuring students' understanding, they gave questions related to the text at the post-reading stage. Beside that, students are trained to create sentences from the word chosen from text, discuss the students' answers, review the lesson and lastly explain the conclusion.